2013
DOI: 10.5402/2013/812964
|View full text |Cite
|
Sign up to set email alerts
|

Impact of a Low-Pressure Polyurethane Adult Endotracheal Tube on the Incidence of Ventilator-Associated Pneumonia: A before and after Concurrence Study

Abstract: Background. Ventilator-associated pneumonia (VAP) is a leading cause of morbidity and mortality in intensive care unit (ICU) patients, encompassing up to 15% of all hospital acquired infections. Our hospital implemented a facility-wide conversion from a low-volume high-pressure polyvinyl cuffed endotracheal tube (PV-cuffed ETT) to a high-volume low-pressure (HVLP) polyurethane-cuffed endotracheal tube (PU-cuffed ETT) in an effort to reduce the incidence of VAP. Methods. We completed an IRB approved, retrospect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…A significant reduction in the median ICU stay was found in patients intubated with PU-cuffed tubes when compared to patients who were on conventional cuffed tubes (17–11 days). [ 10 ] The presence of hospital-acquired pneumonia (HAP) is known to increase hospital stay by 7–9 days. The incidence of HAP is noted to be 20 times higher in patients who are mechanically ventilated.…”
Section: Discussionmentioning
confidence: 99%
“…A significant reduction in the median ICU stay was found in patients intubated with PU-cuffed tubes when compared to patients who were on conventional cuffed tubes (17–11 days). [ 10 ] The presence of hospital-acquired pneumonia (HAP) is known to increase hospital stay by 7–9 days. The incidence of HAP is noted to be 20 times higher in patients who are mechanically ventilated.…”
Section: Discussionmentioning
confidence: 99%
“…Gadani's research showed that 37% of patients hospitalized in the Intensive Care Unit (ICU) became VAP (Gadani et al, 2010). Prolonged use of a ventilator leads to VAP risk, thereby increasing mortality from 5% to 65% (Schweiger et al, 2013) Several factors that influence VAP include the patient's age, length of use of a ventilator, patient consciousness level, comorbid disease, and antibiotic treatment (Wu et al, 2019) Several studies have reported bacterial resistance to antibiotics in humans, animals, and the environment García et al,2020;Hoque et al, 2020). The negative impact of bacterial resistance in humans is that the infection does not recover by antibiotic therapy, more complication, a longer length of stay, higher cost of care, and increased patient mortality rate (Collignon, 2012;(Friedman et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…A previous study reported a shorter ICU stay in patients using PU-cuffed tubes than in patients who used conventional cuffed tubes (17–11 days). 21 Previous studies have suggested that silver-coated ETTs were associated with reduced mortality in patients who developed VAP; however, studies using noble metal–alloy ETTs are limited.…”
Section: Discussionmentioning
confidence: 99%